Pengaruh Terapi Musik Klasik Terhadap Tingkat Depresi pada Lansia di Unit Rehabilitasi Sosial Wening Wardoyo Kecamatan Ungaran Kabupaten Semarang - M. Bambang Marzuki; Puji Lestari (Jurnal Keperawatan Komunitas, 2014)
Depression in the elderly is a frequently psycho-geriatric problem and need special attention. One way to overcome depression in the elderly is by relaxation like listening to classical music. This study aimed to find the influence of classical music therapy in lowering the level of depression on the elderly at the Wening Wardoyo Social Rehabilitation Unit Ungaran Ward. This was a quasi-experimental study with non-equivalent control group design. The population of this study was all elderly at the Wening Ungaran Social Rehabilitation Unit as many as 96 peoples. Data sampling used purposive sampling technique and obtained 36 respondents. The levels of depression were measured by using SDG. The results of this study indicated that before given classical music therapy, the levels of depression of the respondents were mostly in the category of medium that wee 66.7% for the intervention group and 61.1% for the control group. The level of depression after given by classical music therapy in the intervention group was in the category light of 67.7%, whereas in the control group was in the category of medium of 66.7%. There was a difference in the levels of depression on elderly in the intervention group (p-value = 0.003) and there was no difference in the level of depression in the control group (p-value = 0.815). There was an influence of classical music therapy in lowering the levels of depression in the elderly (p-value = 0.037 < α 0.05) in the Wening Wardoyo Social Rehabilitation Unit Ungaran. For the officers in the Wening Wardoyo Social Rehabilitation Unit Ungaran it is expected to apply classical music therapy as an intervention plan in treating depression on the elderly.